The promise of perfect adult tissue repair and regeneration in mammals: Learning from regenerative amphibians and fish. (9th July 2014) - Godwin, James
<x xml:space="preserve">Abstract</x> Regenerative medicine promises to greatly impact on human health by improving repair outcomes in a range of tissues and injury contexts. Successful therapies will rely on identifying both intrinsic and extrinsic biological circuits that control wound healing, proliferation, cell survival, and developmental cell fate. Animals such as the zebrafish and the salamander display powerful examples of near‐perfect regeneration and scar‐free healing in a range of injury contexts not attained in mammals. By studying regeneration in a range of highly regenerative species that maintain regenerative potential throughout life, many instructive and permissive factors have been identified that could assist in the development of regenerative therapies. This review highlights some of the recent observations in immune regulation, epigenetic regulation, stem cell mobilization, and regenerative signatures that have improved our understanding of the regenerative process. Potential opportunities in harnessing this knowledge for future translation into the clinic are discussed.